POPULASI BAKTERI, KUALITAS AIR MEDIA PEMELIHARAAN DAN HISTOLOGI BENIH IKAN GABUS (Channa striata) YANG DIBERI PAKAN BERPROBIOTIK - Dina Eka Trisna; Ade Dwi Sasanti; Muslim . (Jurnal Akuakultur Rawa Indonesia, 2013)
ABSTRACT The aims of this research was to know the effect of fed with addition of probiotic to bacteria population, and water quality of media maintenance, histology of snakehead (Channa striata) fry. This research used randomized completely design (RCD) with six treatments and three repeat with treatments code (D). treatment tested were D0 (control without probiotic), D1 (2.5 ml.kg-1 feed), D2 (5 ml.kg-1 feed), D3 (7.5 ml.kg-1 feed), D4 (10 ml.kg-1 feed), D5 (12.5 ml.kg-1 feed). The research was conducted November to December, 2012 at the Laboratorium Dasar perikanan, Agriculture Faculty Sriwijaya University, Indralaya. Population bacteria, water quality and histology were analyzed descriptively. The result research was conducted that addition probiotic with a cocentration of 10 ml.kg-1 feed in snakehead medium give good influence to survival rate (63.33 %). Histology of intestine were enteritis, loss of epithelial tunica serosa, and histology of lever were congestion, necrosis, hemorrhagic. Â  Key word : Snakehead, probiotic, population bacteria